Pengaruh Pengalaman Kuliner Dan Kualitas Produk Terhadap Brand image Produk Jajanan Tradisional Di Catarina Cake & Coffee Batam - Raudah, Siti; Nuryanto, Heri; Syaiful, Hendra (Journal of Food and Culinary, 2025)
This study aims to determine the effect of culinary experience and product quality on the brand image of traditional snacks at Catarina Cake & Coffee Batam. The type of research conducted is quantitative research based on a survey. Data collection was conducted using a 1-5 Likert scale questionnaire distributed to 150 respondents selected using purposive sampling, namely respondents who had enjoyed traditional snacks at Catarina Cake & Coffee Batam. The research instruments were prepared by identifying the research objectives and variables, conducting validity tests, and reliability tests. Data analysis was performed using classical assumptions (normality, multicollinearity, and heteroscedasticity), t-tests, and F-tests (ANOVA) with the help of SPSS software. The results showed that culinary experience had a significant positive effect on brand image, with a t-value of 2.652 and a significance level of 0.009 (<0.05). Product quality also had a significant positive effect on brand image, with a t-value of 9.403 and a significance level of 0.000 (<0.05). Through the F test (ANOVA), a value of F = 229.981 with Sig. = 0.000 (<0.05) was obtained, indicating that culinary experience and product quality together have a significant effect on brand image. These results prove that the better the culinary experience and the higher the product quality, the stronger the brand image formed in the minds of consumers. The implications of these findings indicate that developing a better culinary experience and product quality contributes to the understanding of the food service business, especially Catarina Cake, by emphasizing the role of innovation and quality as key factors in achieving market excellence.